2015
DOI: 10.1785/0120140272
|View full text |Cite
|
Sign up to set email alerts
|

Improved Regional and TeleseismicP‐Wave Travel‐Time Prediction and Event Location Using a Global 3D Velocity Model

Abstract: A global validation dataset of 116 seismic events and 20,977 associated Pn and P arrivals is used to assess travel-time prediction and event location accuracy for the global-scale, 3D, P-wave velocity model called LLNL-G3Dv3 (Simmons et al., 2012). Strong regional trends that are observed for ak135 travel-time residuals are largely removed when LLNL-G3Dv3 is used for prediction. The 25th-75th quantile spread of travel-time residuals is reduced by 30%-40% at teleseismic distances, and the spread is reduced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The azimuthal gaps of shots 2–12 range from 150° to 220°, whereas shot 1 has a larger azimuthal gap of 320°. Myers et al () showed that epicenter errors increase nearly linearly with azimuthal gap between 0° and 220°, and nonlinearly when the azimuthal gap is larger than 220°. The local earthquakes were recorded by 2‐D seismic arrays and have better azimuthal coverage than the shots.…”
Section: Methodsmentioning
confidence: 99%
“…The azimuthal gaps of shots 2–12 range from 150° to 220°, whereas shot 1 has a larger azimuthal gap of 320°. Myers et al () showed that epicenter errors increase nearly linearly with azimuthal gap between 0° and 220°, and nonlinearly when the azimuthal gap is larger than 220°. The local earthquakes were recorded by 2‐D seismic arrays and have better azimuthal coverage than the shots.…”
Section: Methodsmentioning
confidence: 99%
“…The starting model in the inversion for G3Dv3 included information in RSTT. A recent study investigated the accuracy of G3Dv3 by applying a 3‐D ray tracing to the prediction of P wave arrival time [ Myers et al , ]. This model consists of 57 layers from the surface to the core‐mantle boundary.…”
Section: Modelsmentioning
confidence: 99%
“…One approach is to use tomographic velocity models to predict the travel times of seismic phases more accurately. Several studies have demonstrated improved travel-time prediction accuracy using a global 3-D model (Smith & Ekström 1996;Antolik et al 2001;Chen & Willemann 2001;Myers et al 2015). However, although the obtained velocity information provides enhanced absolute hypocentre locations by reducing the biasing effects of large-scale velocity structure, usually only a smooth model can be obtained, which cannot effectively account for small-scale velocity heterogeneities, particularly when applied to global earthquake location.…”
Section: Introductionmentioning
confidence: 99%